The Role of the Internal Control System in Supporting the Supervision Procedures for Corporate Taxpayer Income Tax Receipt - Suhidayat, Tatang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Problems that occur at the Bandung Bajonagara Tax Service Office in connection with the title that the author adopts, namely an error that occurs in tax reporting by taxpayers, due to a lack of knowledge and understanding of taxpayers, so that the level of taxpayer compliance is less and the state will suffer losses if If the tax revenue target is not achieved, it will result in reduced state revenue from the tax sector. The data collected consisted of primary data and secondary data, collected through documentation studies with an ordinal scale, then the data were analyzed using correlation, termination, and t-test methods. For primary data obtained through the distribution of questionnaires. Then the results that with a significance level of 5% regarding the relationship and role of the internal control system in supporting the procedures for controlling corporate income tax receipts at KPP Bandung Bojonagara, there is a strong, positive, and significant relationship between the internal control system and the procedures for controlling the receipt of corporate income tax. It means that if the internal control system is carried out properly, the supervisory procedure for the receipt of the Agency's PPH will be effective and efficient under the applicable laws and regulations, and vice versa. The internal control system can contribute 70.73% in its role in achieving the effectiveness of the procedures for controlling the receipt of Corporate Income Tax and the remaining 29.27% is influenced by other factors not carried out in the study. Based on these two points, the hypothesis that the author put forward that "The internal control system plays a significant role in supporting the procedures for controlling the receipt of Corporate Income Tax" is acceptable.